SOCIAL SUPPORT RELATIONSHIP WITH SELF CONCEPT IN HIV / AIDS PATIENTS - sri sudarsih; yusarief setiawan (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
A positive self-concept in people with HIV / AIDS is needed. This is because the various problems that occur in people with HIV / AIDS both physical and psychological problems. The concept of self has the role of helping the sufferer achieve his life goal, one way that can be used is through social support from. The purpose of this research is to know the relationship of social support with self concept of HIV / AIDS patient. Independent variable is social support and dependent variable that is self concept. The design of the study used correlation analytic design with cross sectional design. The sample is 26 respondents. The sampling technique uses non probability sampling type consecutive sampling. The instrument uses a questionnaire consisting of a questionnaire to measure social support and to measure self-concept. The Stabilistic Test uses the Fisher's Exact Test. Result of research got most respondent have social support that is 15 respondent (57,7%), most of respondent have positive self concept that is 16 respondent (61,5%). The result p (0,032) and ÃŽÂ± (0,05) which means there is relationship of social support with self concept in patient of HIV / AIDS. The higher the social support the more positive the self-concept, the lower the social support will produce negative self-concept. Counseling for families about social support for people with HIV / AIDS will increase family knowledge so it is expected to develop patient self-concept.